(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
The excavation has provided new information on late medieval to post-medieval development and land use in this part of Leith and provided some insight into the construction techniques for a large house of the 17th century and its services. Two alternative explanations are considered for the presence of the burials.